Characterization and reactivity of iron based nanoparticles synthesized by tea extracts under various atmospheres. (February 2017) - Lin, Jiewen; Weng, Xiulan; Dharmarajan, Rajarathnam; Chen, Zuliang
Abstract: Bio-synthesis of Fe NPs in inert (nitrogen N-Fe NPs) and oxygen (O-Fe NPs) atmospheres employing green tea extracts was investigated through SEM, EDS, XPS and FT-IR techniques. The particle sizes of N-Fe NPs and O-Fe NPs were confirmed by SEM showing 84.7 ± 11.5 nm and 117.8 ± 26.2 nm respectively with subsequent evaluation of the percentage composition of Fe and O by EDS. The XPS results showed that the zero-valent iron and iron oxide nanoparticles were found to be dominant synthesized respectively in nitrogen and oxygen atmospheres. The FT-IR spectra further demonstrated that the surface functional groups of Fe NPs were different by varying the synthesis atmosphere. Fe NPs were used to remove methylene blue (MB) to test the reactivity, and the removal efficiency of MB using N-Fe NPs was 98.7%, while that of O-Fe NPs was only 65.3%. Thus it is clearly demonstrated that the synthesis atmosphere has prominent effects on the formation and catalytic properties of Fe NPs. Highlights: Iron-based nanoparticles (Fe NPs) were synthesized by tea extract. Fe NPs were synthesized under N2 and O2 atmospheres. Different composition, morphology and size of Fe NPs were obtained. Degradation of methylene blue by Fe NPs was tested.